2020
DOI: 10.3389/fchem.2020.00215
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Reductive Amination of Aldehydes and Ketones With Nitro Compounds: New Light on an Old Reaction

Abstract: Reductive amination of carbonyl compounds with primary amines is a well-established synthetic methodology for the selective production of unsymmetrically substituted secondary and tertiary amines. From the industrial and green chemistry perspective, it is attractive to combine reductive amination with the synthesis of primary amines in a single one-pot catalytic process. In this regard, nitro compounds, which are readily available and inexpensive feedstocks, received much attention as convenient precursors to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…49−51 Nitro-compounds are used as precursors in the synthesis of common amines such as aniline, which is produced industrially by the hydrogenation of nitrobenzene at high temperature over a metal catalyst. 38 The reduction of nitro-compounds in tandem with reductive amination using aldehydes or ketones to yield secondary and tertiary amines is a well-known reaction that has been bolstered in the past decade by the development of efficient and selective non-noble metal catalysts, 52 including recent examples using iron oxide and cobalt oxide nanocatalysts. 53,54 Inspired by these reports, we hypothesized that our reductive N-methylation reaction with CO 2 could be made compatible with nitro-compounds as the nitrogen source by reducing them in situ to provide the coupling nucleophile.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…49−51 Nitro-compounds are used as precursors in the synthesis of common amines such as aniline, which is produced industrially by the hydrogenation of nitrobenzene at high temperature over a metal catalyst. 38 The reduction of nitro-compounds in tandem with reductive amination using aldehydes or ketones to yield secondary and tertiary amines is a well-known reaction that has been bolstered in the past decade by the development of efficient and selective non-noble metal catalysts, 52 including recent examples using iron oxide and cobalt oxide nanocatalysts. 53,54 Inspired by these reports, we hypothesized that our reductive N-methylation reaction with CO 2 could be made compatible with nitro-compounds as the nitrogen source by reducing them in situ to provide the coupling nucleophile.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Although electrochemical reductive N-methylation of amines, hydroxylamines, and hydrazine with CO 2 are novel reactions with potential in the sustainable synthesis of fine chemicals, it would be desirable to utilize cheaper and synthetically more accessible nitrogen sources such as nitro-compounds, which are prepared commercially using robust nitration methods. Nitro-compounds are used as precursors in the synthesis of common amines such as aniline, which is produced industrially by the hydrogenation of nitrobenzene at high temperature over a metal catalyst . The reduction of nitro-compounds in tandem with reductive amination using aldehydes or ketones to yield secondary and tertiary amines is a well-known reaction that has been bolstered in the past decade by the development of efficient and selective non-noble metal catalysts, including recent examples using iron oxide and cobalt oxide nanocatalysts. , Inspired by these reports, we hypothesized that our reductive N-methylation reaction with CO 2 could be made compatible with nitro-compounds as the nitrogen source by reducing them in situ to provide the coupling nucleophile. We found that the CoPc/CNT electrocatalyst exhibits good activity for the reduction of nitro compounds to hydroxylamine or amine (Figure S10).…”
Section: Resultsmentioning
confidence: 99%
“…As recently highlighted by Sukhorukov [ 22 ], the RA of carbonyl derivatives with nitro compounds can viewed as an old reaction because more than 80 years ago Major [ 39 ] and Emerson et al [ 40 , 41 ] reported on the coupling of nitroarenes with aldehydes under catalytic hydrogenation over platinum oxide (PtO 2 : Adams’ catalyst [ 42 ]) and Raney Nickel catalyst, respectively. The proposed protocols were generally applicable to both aromatic and aliphatic aldehydes but in most cases low or moderate yields in secondary amines were achieved.…”
Section: Metal-catalyzed One-pot Reductive Amination Reactionmentioning
confidence: 99%
“…The discussion on the various catalysts has been focused also on the advantages of the catalysts in terms of recyclability without forgetting to underline some of their drawbacks. For highlights or reviews dealing with other aspects of reductive amination reactions for the synthesis of several kinds of amines, the reader is referred to the works reported in references [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…[3] Traditionally, N-alkylated amines are synthesized using alkyl halides as alkylating agents, however, this procedure is problematic due to amine over-alkylation, the toxic nature of alkyl halides and related alkylating agents, and also the generation of inorganic salt waste. [1a] Meanwhile, N-substituted amines can be synthesized through the Buchwald-Hartwig amination, [4] reductive amination of aldehyde or ketone, [5] self-coupling of amines, [6] hydroamination, [7] hydroaminomethylation, [8] C-H amination, [9] amine alkylation with alcohol, [10] coupling of oxygen-containing feedstock with NH 3 , [11] and reaction of amines with CO 2 . [12] There is lack of a comprehensive overview on the production of N-substituted amines.…”
Section: Introductionmentioning
confidence: 99%